THE ROLE OF AN INTEGRATIVE APPROACH IN THE DEVELOPMENT OF PROFESSIONAL AND CREATIVE ACTIVITY OF FUTURE PRIMARY CLASS TEACHERS (World Bulletin of Social Sciences, 2023)
Specific topics included in the elementary school "Reading Book" textbooks are determined by the fact that they introduce students to the magical world of fiction, and focus on the correct formation of their worldviews based on the ideology of national independence. Accordingly, the leading feature of the reading classes is to ensure the literacy of the students, as well as to educate the students in the spirit of high moral values based on the national ideology. The subject range of the works studied in the reading lessons of primary grades is quite wide, and they are general, such as mother nature, seasons, folklore, love of work, major holiday dates, national independence and spirituality. are united within the framework of topics